Reorganization of the Production Process from The Complete Knocked-Down Approach to Partial Knocked-Down Production Assembly Method, The Case Study - Monika MAJKA; Arkadiusz KOWALSKI (Communications of International Proceedings, 2024)
The purpose of this article is to present the complexity of the production process transformation and to describe effective methods supporting the reorganization. Implementation of new assembly methods parallel with maintaining production continuity requires proper planning of the production and logistics process and quality and resources management. This paper describes the techniques that allow the organization to re-design and implement the processes according to defined scope. It also focused on cross-functional team cooperation, which is one of the success factors in securing effective problem-solving and preparing the optimal solutions. The transformation process can be executed by many ideas and ways of working, which are mentioned in this article, that's why it describes the importance of the background decision and prerequisites to set the direction. The multidimensional aspect of the presented topic indicates that knowledge of available tools and methods is not enough to perform the transformation without proper preparation and understanding of the strategy of the organization.
Keywords: lean principles; production process reorganization; layout planning; semi-knocked down vehicle